Nigerian Intellectual Property Law : Reform and Development - Lawal-Arowolo, Ayoyemi; Ola, Kunle (Routledge Studies on Law in Africa, 2022)
This book reflects on the development of Nigeria’s intellectual property law and outlines the urgent need for reform. Bringing together expert contributors from around the world, the book identifies and discusses the inadequacies and lacunas in current intellectual property law, and how it is practiced and applied in Nigeria. The book argues that the revision and reform of Nigeria’s intellectual property law will be vital for the country’s development and national interests, whilst also recognising that Nigeria’s legal provisions must sit within a broader global context. Divided into three parts, the book discusses patents, trademarks, and copyright in the context of broad overarching themes affecting all aspects of intellectual property law. Honouring Professor Adebambo Adewopo SAN, the pioneering thinker in Nigerian intellectual property law, this book will be an important resource for researchers working on African Law.
Keywords: immateriaalioikeus; tekijänoikeus; tekijänoikeuslaki; teollisoikeus; tavaramerkit; tavaramerkkilaki; perimätieto; patentit; patenttijärjestelmät; verkkotunnukset; esittävät taiteet; Nigeria